Roles of Negatively Charged Histone Lysine Acylations in Regulating Nucleosome Structure and Dynamics - Jing, Yihang; Li, Xin; Liu, Zheng; Li, Xiang David (Frontiers in Molecular Biosciences, 2022)
The nucleosome, the basic repeating unit of chromatin, is a dynamic structure that consists of DNA and histones. Insights derived from biochemical and biophysical approaches have revealed that histones posttranslational modifications (PTMs) are key regulators of nucleosome structure and dynamics. Mounting evidence suggests that the newly identified negatively charged histone lysine acylations play significant roles in altering nucleosome and chromatin dynamics, subsequently affecting downstream DNA-templated processes including gene transcription and DNA damage repair. Here, we present an overview of the dynamic changes of nucleosome and chromatin structures in response to negatively charged histone lysine acylations, including lysine malonylation, lysine succinylation, and lysine glutarylation.